2023
DOI: 10.1038/s41380-023-02295-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cumulative obstetric complications and childhood trauma on brain volume in young people with psychotic experiences

Kate Merritt,
Pedro Luque Laguna,
Arjun Sethi
et al.

Abstract: Psychotic experiences (PEs) occur in 5–10% of the general population and are associated with exposure to childhood trauma and obstetric complications. However, the neurobiological mechanisms underlying these associations are unclear. Using the Avon Longitudinal Study of Parents and Children (ALSPAC), we studied 138 young people aged 20 with PEs (n = 49 suspected, n = 53 definite, n = 36 psychotic disorder) and 275 controls. Voxel-based morphometry assessed whether MRI measures of grey matter volume were associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 85 publications
0
1
0
Order By: Relevance
“…1b). Individuals who reported operationally-defined psychotic experiences (PEs), whether rated as ‘suspected’ ( PE-suspected , n = 48), ‘definite’ ( PE-definite , n = 73), or ‘clinical’ for those who had experienced additional signs of social impairment or help-seeking ( PE-clinical , n = 36), collectively formed the PE group 31,32 . Individuals who experienced a First Episode of Psychosis (FEP, n = 352) composed the FEP group.…”
Section: Resultsmentioning
confidence: 99%
“…1b). Individuals who reported operationally-defined psychotic experiences (PEs), whether rated as ‘suspected’ ( PE-suspected , n = 48), ‘definite’ ( PE-definite , n = 73), or ‘clinical’ for those who had experienced additional signs of social impairment or help-seeking ( PE-clinical , n = 36), collectively formed the PE group 31,32 . Individuals who experienced a First Episode of Psychosis (FEP, n = 352) composed the FEP group.…”
Section: Resultsmentioning
confidence: 99%
“…A number of pre and perinatal complications have a small yet robust association with an increased risk of developing psychosis ( Davies et al, 2020 ). Exposure to pre- and perinatal risk factors are associated with altered grey matter volume, with recent MRI studies highlighting enlarged striatal and reduced cingulate volumes ( Holz et al, 2023b , Merritt et al, 2023a ). As these regions (cingulate, insula, and striatum) contribute to salience processing, alterations in this network could increase an individual’s propensity to develop a psychotic disorder ( Del Fabro et al, 2021 , Palaniyappan and Liddle, 2012 ).…”
Section: Mechanistic Pathwaysmentioning
confidence: 99%
“…Adults with a history of childhood trauma display reduced grey matter in frontal and limbic networks (Calem et al, 2017; Frodl et al, 2017; Lim et al, 2014b; Paquola et al, 2016; Pollak et al, 2022; Tymofiyeva et al, 2022; Yang et al, 2023), a pattern which is also observed in psychosis patients ( Kim et al, 2015 , Picó-Pérez et al, 2022 , Shepherd et al, 2012 , van Erp et al, 2018 ). Additionally, there is some evidence of increased basal ganglia volume, which may be relevant to psychosis ( Holz et al, 2023b , Merritt et al, 2023a , Popovic et al, 2020 ). These neurodevelopmental abnormalities can increase the sensitivity of the dopaminergic system, particularly in response to stress ( Egerton et al, 2017 , Egerton et al, 2016 ).…”
Section: Mechanistic Pathwaysmentioning
confidence: 99%